ALUR TRANSMISSION OF RELIGIOUS KNOWLEDGE AND ISLAMIC THOUGHT DALAM ISLAMIC THOUGHT; AN INTRODUCTION KARYA ABDULLAH SAEED TERBITAN ROUTLEDGE 2006 - Ahmad Putra (Islam Transformatif : Journal of Islamic Studies, 2019)
This paper describes the fundamental teachings of the Prophet Muhammad, the development of religious knowledge, and the social and political context that shaped the intellectual tradition of Islam. Abdullah Saeed, in the transmission of spiritual experience and Islamic thought, introduced the basic teachings of Islam. The emergence of Islam is closely related to the history of its birthplace, the city of Mecca. Besides, Abdullah Saeed also discussed the beginning of the development of religious knowledge, which was immediately explained by the Qur'an and the emergence of sects that influenced the course of change towards truth. Each of these sects and sects has its doctrine, and if there is anything against it, there is undoubtedly a separate assessment of the differences that are believed. Several groups with various theological or religio-political orientations emerged. Among them are Kharijis (khawarij), Shia, Qadaris (qadariyya), Mu‘tazilis (mu‘tazila), Jabris (jabriyya) and Murji'is (murji'a).